Pengaruh Harga, Kualitas Produk, Dan Citra Merek Terhadap Minat Beli Pelanggan Produk Camille Beauty (Studi Pada Pelanggan Produk Camille Beauty Di Kota Malang) - Abdila, Selvy Aulia Putri; Salim, Muhammad Agus; Millaningtyas, Restu (UNIVERSITAS ISLAM MALANG, 2024)
Abstract The study to examine the effect of prices, product quality, and brand image simultaneously or partially on the buying interest of Camille Beauty product customers. The type of research is explanatory research and uses quantitative approach methods. The sampling technique used is non-probability sampling with a sampling method using purposive sampling technique. The population size in this study used primary data sources as well as data collection method used is a multiple linier regression model using SPSS version 25 data processing application. The sample used in this study show that (1) prices variables, product quality, and brand image have a significant effect simultaneously on the buying interest of Camille Beauty customers in Malang City (2) prices variables do not have a partially significant effect on the buying interest of Camille Beauty customers in Malang City (3) product quality variables have a partially significant effect on the buying interest of Camille Beauty customers in Malang City (4) image variable the brand has a partially significant effect on the buying of Camille Beauty customers in Malang City. Keywords: Price, Product Quality, and Brand Image